Unity as a Prerequisite for a Christian Mission: A Missional Reading of Rom 15:1-12 - Ksenija Magda (Kairos (English Ed.))
This article seeks to show that it is ecclesiologically useful to read Romans primarily as a mission-strategic document. The understanding of Paul’s global mission helps us recognise how, in the paraenesis of the epistle, Paul’s call to unity connects to the pastoral problem of ethnic division among Roman Christians. Unity, it seems, is understood by Paul to be the prerequisite for the success of his world mission. This kind of unity could be equally as important for the Christian witness in a postmodern global village.